Comparison of the Freelite serum free light chain (SFLC) assay with serum and urine electrophoresis/immunofixation and the N Latex FLC assay. Issue 6 (October 2015) - Sasson, S. C.; McGill, K.; Wienholt, L.; Carr, A.; Brown, D. A.; Kelleher, A. D.; Breit, S. N.; Sewell, W. A.
<x xml:space="preserve">Abstract</x> Summary Few reports have compared available serum free light chain (SFLC) assays. Here, a retrospective audit of the Freelite SFLC assay compared results to electrophoresis (EP)/immunofixation (IFX) and the N Latex FLC assay. A total of 244 samples collected over 3.5 months were studied using the Freelite and N Latex FLC nephelometry assays. Results were compared with serum and/or urine EP/IFX. The precision and linearity of the N Latex FLC assay was examined. Detectable paraprotein by serum or urine EP/IFX was present in 94% of samples with kappa and 100% with lambda FLC restriction. The correlation between the assays was higher for kappa (rho = 0.97) than lambda (rho = 0.89) especially when lambda results were above the upper limit of normal (rho = 0.62). Agreement in the categorical diagnosis as measured by the Cohen's kappa statistic was good (0.70). The N Latex FLC assay displayed good precision and linearity. In discordant samples the Freelite and N Latex FLC assays had equivalent agreement with IFX. Traditional methods of EP/IFX detected paraproteins in the majority of cases. Correlation between the Freelite and N Latex FLC assay is better for kappa than lambda FLC. The two assays are not entirely equivalent. Care should be taken by interpreting physicians and laboratories considering switching assays.